Effects of heat treatments on antioxidant capacity and total phenolic content of four cultivars of purple skin eggplants - Athiwat Chumyam (2018)
We investigated the effects of three heat treatments on antioxidant capacity and total phenolic content in purple skinned eggplant fruits. Four cultivars of eggplant: 'Muang Lek', 'Muang Lot Fai', 'Muang Kan Dam', and 'Muang Kan Khiao' were subjected to boiling, steaming, and microwaving for 5, 10, and 15 min in each treatment. The results show that antioxidant capacity (DPPH and ABTS) and total phenolic content significantly increased in all eggplant cultivars with all cooking methods compared with those of raw fruits. Fruits microwaved for 10 and 15 min had the highest antioxidant capacities and total phenolic content in all cultivars. 'Muang Lot Fai' had the highest antioxidant capacity and total phenolic content of the four cultivars examined. A highly positive correlation for each heat treatment was found between antioxidant capacity and total phenolic content.